The sequences encoded by immunoglobulin diversity (DH) gene segments play key roles in controlling B‐cell development, antigen‐binding site diversity, and antibody production. Issue 1 (26th June 2018) - Khass, Mohamed; Vale, Andre M.; Burrows, Peter D.; Schroeder, Harry W.
Summary: Although at first glance the diversity of the immunoglobulin repertoire appears random, there are a number of mechanisms that act to constrain diversity. For example, key mechanisms controlling the diversity of the third complementarity determining region of the immunoglobulin heavy chain (CDR‐H3) include natural selection of germline diversity (DH ) gene segment sequence and somatic selection upon passage through successive B‐cell developmental checkpoints. To test the role of DH gene segment sequence, we generated a panel of mice limited to the use of a single germline or frameshifted DH gene segment. Specific individual amino acids within core DH gene segment sequence heavily influenced the absolute numbers of developing and mature B‐cell subsets, antibody production, epitope recognition, protection against pathogen challenge, and susceptibility to the production of autoreactive antibodies. At the tip of the antigen‐binding loop (PDB position 101) in CDR‐H3, both natural (germline) and somatic selection favored tyrosine while disfavoring the presence of hydrophobic amino acids. Enrichment for arginine in CDR‐H3 appeared to broaden recognition of epitopes of varying hydrophobicity, but led to diminished binding intensity and an increased likelihood of generating potentially pathogenic dsDNA‐binding autoreactive antibodies. The phenotype of altering the sequence of the DH was recessive for T‐independent antibody production, but dominant for T‐cell‐dependent responses. Our work suggests that the antibody repertoire is structured, with the sequence of individual DH selected by evolution to preferentially generate an apparently preferred category of antigen‐binding sites. The result of this structured approach appears to be a repertoire that has been adapted, or optimized, to produce protective antibodies for a wide range of pathogen epitopes while reducing the likelihood of generating autoreactive specificities.